Tarlac, Kidapawan kooperatiba - Aguilar, Mila D. (Pinoy Tok, 1989)
Compares two successful farmers' cooperatives, one managed by former NPA Commander Dante in Capas, Tarlac, and the other was started by a priest in Kidapawan, North Cotabato.